Identification of Fishermen Household’s Adaptive Capacity in Responding to Climate Change Impacts (A Case Study of Muncar District, Banyuwangi Regency, Indonesia) - Fitriawati Fitriawati; Djoko Santoso Abi Suroso (The Indonesian Journal of Planning and Development, 2017)
Climate change affects the uncertainty of oceanographic condition that has an impact on the marine fisheries, such as changes in fishing areas, winds, and extreme waves. As an archipelagic country, the majority of Indonesian cities are in the coastal area whose the community’s livelihood depends on marine fishery activities. Climate change impacts the coastal community who engages in fishery activities are now being vulnerable group towards climate change. This condition is also experienced by fishermen in Muncar District, the second biggest fishery port in Indonesia. It is necessary to enhance fishermen household’s adaptive capacity which is the key to region’s resilience. This research focuses on adaptive capacity assessment by formulating criteria and indicators based on the expert's theories review. The method that is used in this research is statistic descriptive based on a questionnaire which distributed to 120 households samples. This research also views perception of fishermen on climate change impacts and on how Local Government Units (LGUs) and Community Organizations (COs)support the increase of fishermen household’s adaptive capacity. The result of the assessment showed that 56% of households have ‘medium’ adaptive capacity, 34% of them are in ‘low’ adaptive capacity, and 10% households are in ‘high’ adaptive capacity. The LGUs and COs gives a high endorsement to households to increase their adaptive capacity. The result of this study can be taken into consideration in formulating the strategies to enhance fishermen household’s adaptive capacity in order to realize the resilient fishermen households socially and economically.